Strategic Alternatives to Improve the Readiness of Omani Higher Education Institutions to Offer Massive Open Online Courses (MOOCs) - Al- Ani, Wajeha Thabit; Al- Harthi, Aisha Salem; Al- Kindi, Iman Rashid (Journal of Educational and Psychological Sciences, 2021)
The study aimed to investigate the readiness of higher education institutions to offer Massive Open Online Courses (MOOCs) from the perspective of academic leaders in the Sultanate of Oman, and suggested some alternative strategies for development. Data is collected from 38 academic leaders through semi- structured interviews. Results reveal that among the strengths is the existence of an ambitionious and strong desire to plan for the use of technology in teaching in the future, and to further improve the reputation of academic institutions to excel in online education. As for the weaknesses, there is absence of a clear policy for online education, and lack of a clear vision for the nature of MOOCs courses. The study adopts an entrepreneurial strategy, based on strengths and opportunities, and provieds a set of recommendations.
Keywords: Alternatives Strategies; entrepreneurial strategy; readiness; MOOCs